Critical evaluation of the MitraClip system in the management of mitral regurgitation - Deuschl, Florian (Vasc Health Risk Manag, 2016)
The MitraClip (MC) system is a device for percutaneous, transseptal edge-to-edge reconstruction of the mitral valve (MV) in patients with severe mitral regurgitation (MR) not eligible for surgery. Recently, a number of studies have underlined the therapeutic benefit of the MC system for patients with extreme and high risk for MV surgery suffering from either degenerative or functional MR. The MC procedure shows negligible intraprocedural mortality, low periprocedural complication rates, and a significant reduction in MR, as well as an improvement in functional capacity and most importantly quality of life. Presently, the MC system has become an additional interventional tool in the concert of surgical methods. It hereby enlarges the spectrum of MV repair for the Heart Team. Lately, many reviews focused on the MC system. The current review describes the developments in the treatment of MR with the MC system.